Effects of Social Network, Social Trust, and Social Participation on Depression: A Meta-Analysis - Alifia Nadhimah Putri; Shafa Latifah; Virdaria Andriani; Bhisma Murti; Siti Mar’atul Munawaroh (Journal of Epidemiology and Public Health, 2024)
Background: An estimated 3.8% of the population is depressed, including 5% of adults (4% in men and 6% in women), and 5.7% of adults over the age of 60. Around 280 million people in the world are depressed (World Health Organization, 2023). Depression not only impairs functional abilities, lowers the quality of life, and increases the mortality rate of the elderly, but also poses a heavy economic burden on the elderly themselves, the community, and the health care system. This study aims to determine the effects of social network, social trust, and social participation on depression.Subjects and Method: The meta-analysis study was carried out according to the PRISMA flowchart and the PICO model. Population: adults. Intervention: high social network, high social trust, and high social participation. Comparison: low social network, low social trust, and low social participation. Outcome: Depression. The basic data used involves Google Scholar, PubMed, BMC, Science-Direct, and Springer Link. Multivariate analysis criteria that attach aOR values. Data analysis using the Review Manager 5.3 application.Results: Seven primary studies were used to analyze trust with depression. Adults with high trust may lower depression 0.80 times compared with low trust (OR= 0.80; 95% CI = 0.76 to 0.83); p<0.001). Five primary studies were used to analyze social participants with depression. Adults with high social participation may reduce depression by 0.81 times compared to low social participants (OR= 0.81; 95% CI= 0.75 to 0.88; p<0.001). Four primary studies were used to analyze social networks with depression. Adults with high social networks may reduce depression by 0.62 times compared with low social networks (OR= 0.62; 95% CI= 0.57 to 0.68; p<0.001).Conclusion: Social networks, social trust, and social participation reduce depression in adults.